FORMATION OF NANOSTRUCTURES IN SEMICONDUCTORS AND THEIR THIN FILMS - Eshboltayev Iqbol Mamirjonovich,; G‘ofurov Saidkamol Zokirjon ogli,; Eshboltayev Ikromjon Iqbol ogli, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This  paper  presents  a  scientific  analysis  of  the  mechanisms  of  nanostructure formation in semiconductor materials and their thin films. The physicochemical factors influencing the formation of nano-scale structures, epitaxial growth processes, surface energy,  and  diffusion  phenomena  are  discussed.  In  addition,  the  significance  of nanostructured thin films in modern electronics and photonics is demonstrated.